Exploring students' conceptions of the racial and socio-cultural differences in the learning environment of a medical specialty - Wamono, Aye Aye (Department of Health Sciences Education, 2019)
Study problem In the education of South African postgraduate medical specialities, various challenges that could have negative impacts on learning are evident. Racial and socio-cultural diversity in South Africa has roots in a previous societal structure that systematically discriminated against particular social groups resulting in significant political, economic and social inequalities between the groupings. With the current processes of transformation underway, the sphere of training postgraduate students in medical specialities reveals visible differences in racial backgrounds between students and consultants at the training centres across the nation, with the majority of consultants being Whites and Indians, whilst the majority of students are Black Africans and a few Indians. The recent high failure rate of the summative exit examination in certain specialities has stimulated a high level of interest into how racial and socio-cultural diversity may have influenced the training and learning of postgraduate students or registrars. Theoretical framework In this thesis, a conceptual framework is used that combines dimensions from the theories of Collins (1987), Collins, Brown and Holum (1991) on cognitive apprenticeship, Vygotsky (1978), Lave and Wenger (1991) on socio-cognitive and socio-cultural learning, and Bronfenbrenner’s (1977) theory on Human Ecology. Collectively they posit that relationships are central to the quality of learning and training. The education of postgraduate students, so called registrars or intermediary novices, is structured as personal mentoring in the form of cognitive apprenticeship and their legitimate participation in the departmental Community of Practice. Learning in this context occurs through daily service provision under supervision or mentorship, as well as unscheduled informal discussions (engagement) that reflect socio-cultural learning in which novices and consultant specialists interact socially and academically. This form of learning is dependent on effective mediation and participation, which depends upon understanding, trust and mutual respect in a relationship between the two parties. This relationship could be influenced by factors such as inter-personal differences. Whether the factors translate into socio-cultural differences such as language, culture and social identities, need to be determined. Aim and objectives The aim of the study was to explore the conceptions of two student groups, one who had left the specialist programme, and the other who had recently qualified, regarding the nature of racial and socio-cultural diversity in their learning environment, the influences on their learning, and how they responded to them. Methodology Using one of the medical speciality disciplines as a focus area, a qualitative enquiry using faceto-face in-depth interviews followed by a thematic analysis of descriptive data was employed. Participants were former students who had either left the formal training programme after being unsuccessful in the summative examination and reached the end of their employment contracts, or those who had recently passed the examination and qualified as junior specialists. The interviews were semi-structured to explore participant’s learning background through schooling, undergraduate and postgraduate studies, with focus on experiences in formative learning through these stages. The participant’s family socio-cultural background was also explored. Data analysis and interpretation were done using a social constructionist epistemology where meanings were co-constructed based on multiple perspectives Findings and analysis The following themes were identified from the data analysis: Theme 1: Racial and socio-cultural differences as barriers in learning, with the sub-themes: constructing ‘race’, ‘language’, ‘culture’, and ‘feeling excluded by social status’ as barriers to learning; Theme 2: Relationships in the learning environment shaping learning, with sub-themes: ‘relationships in the early learning stage’, ‘relationships in undergraduate medicine’, and ‘relationships in postgraduate learning stage of speciality training’; Theme 3: Challenges in the learning process, with sub-themes as: ‘lack of curricular clarity’, and ‘lack of formative learning structure’; Theme 4: Resilience, with sub-themes: ‘capacity for adaption’, and ‘the ways in which resilience has been shaped by the micro- and macro-environments’. The further analysis found the socio-cultural diversity and relationships affecting engagement during formative learning themes to be inter-related, whilst sub-themes race, language, culture and social identities were also inter-connected. The curriculum, formative training, relationships, people’s perspectives and culture of the community were found to be intricate and complex, yet difficulties could still be overcome using certain attributes and skills. Conclusion Participants perceived the racial and socio-cultural diversity such as language, culture, personality and socio-economic status in the postgraduate learning environment as barriers to learning. Participants in the group who had qualified were however able to negotiate the diversity by being resilient, adaptable and emotionally mature. These attributes enabled them to navigate difficulties and remain focussed on their goal. An ability to initiate and form relationships with new peers and consultants emerged as an important feature in this group. These findings could hopefully benefit both current and future students and highlight the need to create opportunities for cross-cultural engagement activities in medical speciality training programmes.